2016
DOI: 10.1016/j.fuel.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Optimized rate expressions for soot oxidation by OH and O2

Abstract: The two principal soot oxidizers in flames are the hydroxyl radical (OH) and molecular oxygen (O 2). Many soot oxidation rate expressions exist for these oxidizers, but they have considerable disparity and have not been sufficiently validated. To address this, twelve published experimental studies in diffusion flames, premixed flames, thermogravimetric analyzers, and flow reactors are examined. These are all the known studies that measured all of the following quantities at discrete locations: soot oxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…The soot oxidation by OH and O2 was also included. A constant collision efficiency γOH of 0.13 is assumed by OH radicals [78] while soot oxidation rates with O2 were taken from Celnik et al [79], although several recent studies suggested that the oxidation rates of soot depend on its chemical composition and internal structures [80][81][82][83]. Particle aggregation and fragmentation was not considered in this work.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The soot oxidation by OH and O2 was also included. A constant collision efficiency γOH of 0.13 is assumed by OH radicals [78] while soot oxidation rates with O2 were taken from Celnik et al [79], although several recent studies suggested that the oxidation rates of soot depend on its chemical composition and internal structures [80][81][82][83]. Particle aggregation and fragmentation was not considered in this work.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…First, it will decrease the availability of oxygen during the late cycle, which could limit the oxidation rate. It also lowers the flame temperature, slowing the chemical kinetics of the oxidation process as well as decreasing the formation of hydroxyl radicals (OH) [5], which is believed to be the main oxidizing species [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the current soot oxidation model, partial-equilibrium (OH) model and instantaneous (O 2 ) model are used. Although there has been a long debate over the years about the selection of oxidizers for soot, recent studies have proven that for premixed and diffusion flames, the models indicate that soot oxidation by OH dominates over that by O 2 (Guo et al, 2016). The forming of soot in a flame is essentially a chemically controlled phenomenon.…”
Section: Modeling Soot and Radiationmentioning
confidence: 99%
“…The kinetics and mechanisms of soot oxidation have been studied for decades, and it was found that the primary soot oxidizers in the flame are OH radical and O 2 along with a few other minor species such as O radical (Khosousi and Dworkin, 2015;Siegla, 2013). Recent studies have shown that the OH radical plays much more important role than O 2 in soot oxidation (Lee et al, 2009;Guo et al, 2016). Discrete ordinate and P1 radiation models in ANSYS Fluent were tested separately to account for radiation losses in the flame.…”
Section: Modeling Soot and Radiationmentioning
confidence: 99%